Personal Adjustment Santri Scale (PASS): Pengembangan Instrumen Penyesuaian Diri Santri di Pondok Pesantren - Muthi'ah, Shafiyyah; Islam, Azizah Fajar (Indonesian Journal of Counseling and Development, 2025)
This study aims to develop a personal adjustment measurement tool specifically designed for santri (Islamic boarding school students) in pondok pesantren (Islamic boarding schools). The adjustment process for santri involves unique challenges arising from the boarding system, pesantren culture, and both internal and external demands, which differ from those faced in regular school settings. The instrument was developed based on Schneiders’ (1955) Adjustment Theory, with six dimensions contextualized to the santri experience: academic, social, dormitory life, emotional, moral, and sexual adjustment. A quantitative approach was employed following the scale development procedures proposed by DeVellis and Cohen & Swerdlik (2017). The initial instrument, consisting of 26 questionnaire items, underwent readability testing with 30 santri, followed by expert judgment from four professionals for content validity. Empirical testing was conducted with 300 santri from four pesantren in South Tangerang using Confirmatory Factor Analysis (CFA) and reliability testing. The results demonstrated a good model fit (CFI = 0.95; RMSEA = 0.056; SRMR = 0.059) and high reliability (α = 0.877). The instrument was proven to be valid and reliable for measuring santri adjustment and may serve as an early identification tool and the basis for psychological interventions in pesantren. The PASS can be practically used by school counselors, boarding supervisors, and Islamic educators to monitor santri adjustment and provide timely psychosocial support. This study also contributes theoretically to the development of educational psychology grounded in Islamic values in Indonesia.